A refuge assured [large type] - Green, Jocelyn (Center Point Large Print, 2018)
"Endangered in revolutionary France, lacemaker Vivienne Rivard flees to Philadelphia, only to face similar peril from revolutionary sympathizers. Militiaman Liam Delaney just wants to cultivate his hard-won farm near the French settlement of Azilum. When he meets Vivienne, they will be drawn together in surprising ways to fight for the peace and safety for which they long."--